Free Post-MI Medications Improve Adherence without Added Costs - Vinall, Maria (MD Conference Express, 2011)
Researchers recommended widespread adoption of a program that eliminates copayments for preventive medications after the Post-Myocardial Infarction Free Rx Event and Economic Evaluation trial [MI FREEE; NCT00566774] showed that the policy improved treatment adherence without increasing overall health costs.